(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Thematic Lecture presented to the Physiological Society of Nigeria at its 41st Annual Scientific Meeting held at the Rivers State University, Port-Harcourt, Rivers State from February 11 - 17, 2024